Gilliamesque : a pre-posthumous memoir : TG's bio(degradable) autography : a singular person's first first person singular palin-dromic biograph : my me, me, me memoir /: a pre-posthumous memoir : TG's bio(degradable) autography : a singular person's first first person singular palin-dromic biograph : my me, me, me memoir. (2015) - Gilliam, Terry
No abstract available